Morphogenesis of liver epithelial cells. Issue 10 (11th March 2016) - Tanimizu, Naoki; Mitaka, Toshihiro
Abstract : The mammalian liver is a physiologically important organ performing various types of metabolism, producing serum proteins, detoxifying bilirubin and ammonia, and protecting the body from infection. Those physiological functions are achieved with the 3D tissue architecture of liver epithelial cells. The liver contains two types of epithelial cells, namely, hepatocytes and cholangiocytes. They split from hepatoblasts (embryonic liver stem cells) in mid‐gestation and differentiate into structurally and functionally mature cells. Analyses of mutant mice showing abnormal liver organogenesis have identified genes involved in liver development. In vitro culture systems have been used to examine the mechanism in which each molecule or signaling pathway regulates the morphogenesis and functional differentiation of hepatocytes and cholangiocytes. In addition, liver epithelial cells as well as mesenchymal, sinusoidal endothelial and hematopoietic cells can be purified from developing livers, which enables us to perform genome‐wide screening to identify novel genes regulating epithelial morphogenesis in the liver. By combining these in vivo and in vitro systems, the liver could be a unique and suitable model for revealing a principle, governing epithelial morphogenesis. In this review, we summarize recent progress in the understanding of the development of liver epithelial tissue structures.